O interesie narodowym i racji stanu – rozważania teoretyczne - Kałążna, Klaudia; Rosicki, Remigiusz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
The concepts of national interest or raison d’etat continue to be fundamental elements in the foreign policies of states. Making direct reference to these concepts is crucial for making the arguments employed in political discussions efficient. The paper presents theoretical considerations on the issue of raison d’etat or national interest. It attempts to distinguish between the meanings of these two concepts, presents the changes in how they have been understood and tries to approach them theoretically. It also refers to how the raison d’etat and national in- terest are understood by N. Machiavelli, C. Le Bret and a range of contemporary authors. The theoretical approach to national interest makes use of V. Udalov’s theory, which discusses this concept as understood by researchers from the two opposing blocs at the time of the Cold War – the USA and the USSR. The paper also refers to the concept of interest in the context of international relations.
On the national interest or raison d’etat – theoretical considerations
Keywords: interes narodowy; racja stanu; interes polityczny